The Effect of Single Leg Depth Jump and Half Squat Jump Training on the Smashing Ability of Volleyball Athletes in Jeneponto - Malik, Junaedi; Nawir, Nukhrawi; Jamaluddin, Jamaluddin; Hudain, Muh. Adnan; Bismar, Ahmad Rum (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research is experimental research to determine whether or not there is an effect of the application of single leg depth jump and half squat jump training on the volleyball smash ability of Jeneponto athletes. The independent variables in this study are single leg depth jump training and half squat jump training, while the dependent variable is the volleyball smash ability of Jeneponto athletes. The number of samples is 26 samples with the experimental group of single leg depth jump training as many as 13 athletes and half squat jump training 13 athletes. The research data were obtained by providing single leg depth jump and half squat jump training in the form of pretest and posttest. The data analysis technique is by t-test analysis. Based on the results of the statistical analysis of the t-test, P = 0.000 is obtained, which is smaller than α = 0.05. It can be concluded that the application of single leg depth jump and half squat jump training has a significant effect on the volleyball smash ability of Jeneponto athletes.